2012
DOI: 10.1111/j.1600-0463.2012.02942.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of growth factors and growth factor receptors in gastric adenocarcinoma

Abstract: We evaluated growth factors/receptors expression in gastric adenocarcinoma. Immunohistochemistry was used to evaluate epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), VEGF-D, VEGF receptor (VEGFR)-2, VEGFR-3, transforming growth factor (TGF)-α, TGF-β1, and TGF-β-RII in tissue microarrays of adenocarcinoma, dysplasia, metaplasia, and gastritis. In adenocarcinoma, the expression rates of EGFR, VEGF, VEGF-D, VEGFR-2, VEGFR-3, TGF-α, TGF-β1, and TGF-β-RII were 2.0%, 0%, 10.7%, 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Visual inspection also indicates that the expression of VEGFR2 within each diseased area is variable, as is the expression among all of the tumors in a single mouse. This has been shown in previous studies on VEGFR2 expression in colon cancer [42][43][44][45][46]52 and in our own histological evaluation of the colons as demonstrated in Fig. 3.…”
Section: In-vivo Labeling/ex-vivo Imagingsupporting
confidence: 60%
See 1 more Smart Citation
“…Visual inspection also indicates that the expression of VEGFR2 within each diseased area is variable, as is the expression among all of the tumors in a single mouse. This has been shown in previous studies on VEGFR2 expression in colon cancer [42][43][44][45][46]52 and in our own histological evaluation of the colons as demonstrated in Fig. 3.…”
Section: In-vivo Labeling/ex-vivo Imagingsupporting
confidence: 60%
“…It has been shown that vascular endothelial growth factor receptor 2 (VEGFR2) is upregulated in many cancers, including colorectal, as it is important in tumor angiogenesis. [42][43][44][45][46][47] Currently, VEGFR2 is considered a predictor for clinical outcome and in some instances is used for targeted therapy with antiangiogenic drugs. 43,44,[48][49][50] For these reasons, quantum dots bioconjugated to VEGFR2 antibodies have the potential to provide contrast between normal colon and neoplastic lesions as well as a mechanism for evaluating the molecular changes of colorectal tumors in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of surveillance, some of the biomarkers may represent potential prognostic indicators, able to differentiate patients according to the risk of recurrence, and potential early markers of tumor relapse. Among the prognostic markers, the expression of vascular endothelial growth factor, a regulator of angiogenesis, has been associated with a poor prognosis by several authors[60,61]. VEGF receptors are the targets of novel monoclonal antibodies that are currently being evaluated in clinical trials as potential treatments for advanced gastric cancer, such as ramucirumab and bevacizumab[62,63].…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…For example, Kim et al (42) evaluated the expression of various growth factors/receptors in gastric adenocarcinoma, including EGFR, VEGF, VEGF-D, VEGFR-2, VEGFR-3, TGF-α, TGF-β1 and TGF-β RII, using a log rank test to identify that VEGF-D and VEGFR-2 expression was associated with patient survival, and Cox regression analysis to determine that advanced stage gastric cancer and positive expression of VEGF-D were poor prognostic factors. Thus, in gastric adenocarcinoma, VEGF-D expression levels may be of prognostic value, whereas the expression levels of the EGFR and TGF family may have only a minor effect.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%